Argumentación jurídica de las medidas cautelares en el arbitraje ecuatoriano y la competencia de jueces y árbitros para dictarlas y ejecutarlas - Macías Castro, Miryan Graciela (2014)
This legal research work is titled "LEGAL ARGUMENT OF INTERIM MEASURES IN ECUADOR ARBITRATION AND COMPETITION FOR JUDGES AND REFEREES” dictate and implemented, which aims to bring reform to our Law Arbitration and Mediation, with order to guarantee the fundamental rights of creditors who justify and substantiate his credit that he has been at risk, thereby strengthening the development of the arbitration process and its results. The issue is the lack of express provision to identify precisely the time when especially the ordinary courts have jurisdiction to issue and implement precautionary measures in the pre arbitration phase, whose purpose is to allow people who meet the two elementary to grant interim measures budgets, can exercise the right to apply these measures and get these guarantees before the tribunal is constituted arbitral.- The theoretical framework provides a compilation of legal doctrine and major general, Ecuadorian law, foreign and jurisprudence on precautionary measures in the Ecuadorian arbitration jurisdiction of judges and arbiters. Based on a thorough analysis of the findings, conclusions and recommendations to solve the problem and demonstrate the veracity of the hypotheses were generated, and based on the critical analysis of a proposed solution to this problem is issued that can bridge this gap law that affects Ecuadorian citizenship